The protective effect of Boesenbergia rotunda extract on cisplatin-exposed human embryonic kidney-293 cells by inhibiting the expression of kidney injury molecule-1, neutrophil gelatinase associated-lipocalin, NF-κB, and caspases - Dani Sujana; Nyi Mekar Saptarini; Sri Adi Sumiwi; Jutti Levita (Journal of HerbMed Pharmacology, 2023)
Introduction: Acute kidney injury (AKI) is a major problem in platinum-based chemotherapy patients. Boesenbergia rotunda can induce the generation of osteoblast cells and significantly increase pancreatic antioxidant enzyme activities; therefore, this study aimed to investigate the cytotoxicity of cisplatin on human embryonic kidney-293 (HEK-293) cells and the protective impact of the ethanol extract of B. rotunda (EEBR) against such conditions. Methods: Cytotoxicity was assessed using the CCK-8/WST-8 reagent, while the protective activity was assayed on 1 µg/mL cisplatin-exposed HEK-293 cells by quantifying the expression of nephrotoxicity biomarkers, e.g., kidney injury molecule-1 (Kim-1) and neutrophil gelatinase associated-lipocalin (NGAL), nuclear factor-kappaB (NF-κB), apoptotic caspase-3, and caspase-7 genes, in cisplatin-exposed HEK-293 cells. Results: Cisplatin was confirmed as highly toxic against the HEK-293 cells (IC50 = 2.5145 μg/ mL), whereas quercetin was of moderate toxicity (IC50 = 185.6225 μg/mL). EEBR revealed an IC50 = 40.0655 μg/mL. Moreover, EEBR concentrations of 5, 10, and 20 µg/mL confirmed its remarkable protective activity against cisplatin-exposed HEK-293 cells (P=0.031, 0.014, 0.046, respectively) compared to the cisplatin-treated cell lines without treatment. The quantitative real-time polymerase chain reaction (PCR) revealed that a higher concentration of EEBR significantly suppressed the expression of Kim-1, while lower concentrations of EEBR significantly inhibited NGAL and NF-κB genes. Higher concentrations of EEBR reduced the expression of caspase-3. All concentrations of EEBR stimulated the expression of caspase-7. Conclusion: The significant protective activity observed in this study indicated that EEBR might be beneficial in protecting kidney cells against cisplatin.